(untitled) (Conference Zone, 2022)
This article discusses the criteria for preparing textbooks in higher education organizations in the field of technology using BIM technologies and the relevance of monitoring the quality of construction management, and the development of BIM technologies in new construction engineers. The introduction of BIM technologies for improving the staff training system in the fields of architecture and construction engineering is a very important factor for further development of the educational process in the strategic development of construction